2007
DOI: 10.1164/rccm.200607-940oc
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Airway Acidification in Asthma Using Induced Sputum

Abstract: Patients with asthma show lower pH than healthy subjects. Patients with poorly controlled asthma seem to have the lowest induced-sputum pH, independent of the GINA (Global Initiative for Asthma) severity level. In conclusion, induced sputum is a feasible, repeatable, noninvasive method to measure airway pH. The pH in induced sputum may reflect a different aspect of asthma from sputum eosinophils and be related to different pathophysiologic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…Previous studies have shown that airway acidification is a well-recognized symptom in asthma and contributes to the pathophysiology of the disease (26,40). The pH of the airway of healthy subjects is in the range of 7.5 to 7.7, and that of patients with asthma is from 5.2 to 7.1, depending on the severity (26,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that airway acidification is a well-recognized symptom in asthma and contributes to the pathophysiology of the disease (26,40). The pH of the airway of healthy subjects is in the range of 7.5 to 7.7, and that of patients with asthma is from 5.2 to 7.1, depending on the severity (26,40).…”
Section: Discussionmentioning
confidence: 99%
“…The pH of the airway of healthy subjects is in the range of 7.5 to 7.7, and that of patients with asthma is from 5.2 to 7.1, depending on the severity (26,40). It is known that protons sensitize the capsaicin-sensitive TRPV1 channel and/or ASICs in sensory nerves, producing local axonal reflexes with the subsequent release of tachykinins for the induction of cough and other asthmatic symptoms (17,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory acidosis has been observed in several respiratory diseases, such as chronic obstructive pulmonary disease (COPD) and asthma. 12,[61][62][63] Asthma is a chronic inflammatory disease, which is associated with bronchial hyper-responsiveness, airway inflammation, remodeling, and acidic features. Ichimonji et al demonstrated in human airway smooth muscle cells that GPR68 mediated extracellular acidification-induced production of pro-inflammatory cytokine IL-6 and increased intracellular Ca 2+ concentration.…”
Section: Role For the Ph-sensing Gpcrs In The Respiratory Systemmentioning
confidence: 99%
“…Recent evidence suggests that abnormal airway pH may be a determinant of lung disease [3][4][5][6][7][8]. Mature alveolar type-II cells secrete surfactant at low pH (,3-5) [6].…”
mentioning
confidence: 99%